(3GdchcH GdKGbH aj CNHGQ GdTYQGA hZjQge ef Phj GdefGbHs - (3YHO GdbGOQ GdSdhjs ((3GdYjGT Hf YHO Gddg GdedGbi s)
(3ChdgG (B:s
(3fMeOc jG ef GfWb dSGf GdEfSGf HLhGeY Gdcde hHOGFY GdMce s
(3BNQgG (B:s
(3bhdg Udi Gddg Ydjg hSde (B: (3UGQce OYGejU GdLfI hbO Je GdcJGH GdeHGQc s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs